Apiotrichum veenhuisii isolated from a pediatric patient with acute myeloid leukemia: The first case in humans - Lara, Bruna Rossini; Araujo Melo, Milena Barrocali de; Paula, Claudete Rodrigues; Arnoni, Mariana Volpe; Simoes, Cirilo Cesar Naozuka; Nakano, Shirley; Richini-Pereira, Virginia Bodelao; Garces, Hans Garcia [UNESP]; Maciel da Silva, Bosco Christiano; Anversa, Lais; Silva, Eriques Gonsalves; Auler, Marcos Ereno; et al. (Taylor & Francis Inc, 2019)
This is the first report of the yeast Apiotrichum veenhuisii (formerly Trichosporon veenhuisii) causing disease in humans; its virulence and in vitro behavior against antifungals were also studied. The sample was isolated from biopsy fragments of disseminated lesions on the skin of a pediatric patient with acute myeloid leukemia. The studied virulence factors evidenced that the strain tested negative for secretion of the enzymes proteinase, phospholipase, and hemolysin. The isolate was characterized as low biofilm producer. Except for amphotericin B and voriconazole, the sample presented high minimum inhibitory concentration values against azole and echinocandins.
Keywords: Antifungals; biofilm; cancer; enzymes; nosocomial infection; skin lesion; Tremellomycetes; yeasts